Responsiveness of Volatility Analysis of the Jakarta Islamic Index on Macroeconomic Variables - Susanti, Eni; Agriyanto, Ratno; Musahadi, Musahadi; Zuhri, Saifudin (IAIN Salatiga, 2021)
This study aims to analyze the inï¬‚uence and response of the Jakarta Islamic Index (JII)Â volatility to changes in macroeconomic variables. VECM was used to examine the long-andÂ short-term eï¬€ects, while IRF was used to analyze the JII response. Data were obtained fromÂ BPS, BI, and Yahoo Finance monthly from 2015-2020 using global macroeconomic ï¬scalÂ variables, including inï¬‚ation, BI and Exchange Rates, Industrial Production Index, World OilÂ Price, Malaysia Hijrah Shariah Index, and DJIM Malaysia Titan 25 Index. The results showÂ that JII is inï¬‚uenced by inï¬‚ation variables, BI rate, IPI, OP, MHS, and DJIM in the long termÂ but not the exchange rate. Furthermore, it is inï¬‚uenced by BI rate, IPI, OP, MHS, and DJIM inÂ the short term, while the exchange rate and inï¬‚ation have no signiï¬cant eï¬€ect.Â Macroeconomic variable shock inï¬‚uence JII by 52,27% while the rest is inï¬‚uenced by otherÂ variables outside the model. This research implies that the JII index is very sensit ive toÂ economic changes.